Cloning and expression of a Kv1.2 class delayed rectifier K+ channel from canine colonic smooth muscle. - Hart, P J (1993)
A cDNA (CSMK1) encoding a delayed rectifier K+ channel of the Kv1.2 class was cloned from canine colonic circular smooth muscle and expressed in Xenopus oocytes. These channels appear to be uniquely expressed in gastrointestinal muscles and may participate in the electrical slow wave activity. Functional expression of CSMK1 in Xenopus oocytes demonstrated a K+ current that activated in a voltage-dependent manner upon depolarization. This current was highly sensitive to 4-aminopyridine (IC50, 74 microM). A low-conductance K+ channel was identified in inside-out patches from oocytes injected with CSMK1. This channel displayed a linear current-voltage relation with a slope conductance of 14 pS. The channels were blocked in a concentration-dependent manner by 4-aminopyridine. Northern blot analysis demonstrated that CSMK1 is expressed in a wide variety of gastrointestinal smooth muscles. Portal vein, renal artery, and uterus do not express CSMK1, suggesting that, among smooth muscles, expression of this K+ channel may be restricted to gastrointestinal smooth muscles. CSMK1 is 91% homologous to RAK, a delayed rectifier K+ channel cloned from rat heart, but displays unique pharmacological properties and tissue distribution.